Control of intramolecular singlet fission in a pentacene dimer by hydrostatic pressure. Issue 12 (6th March 2023) - Kinoshita, Tomokazu; Nakamura, Shunta; Harada, Makoto; Hasobe, Taku; Fukuhara, Gaku
Abstract : We investigated singlet fission (SF) effects of a biphenyl-bridged pentacene dimer upon hydrostatic pressurization, revealing that the desolvation process in polar solvents plays an important role in the SF dynamics under high pressure. Abstract : Singlet fission (SF), which produces two triplet excitons from a singlet exciton, has been identified as a novel nanointerface for efficient (photo)energy conversion. This study aims to control exciton formation in a pentacene dimer through intramolecular SF using hydrostatic pressure as an external stimulus. We reveal the hydrostatic-pressure-induced formation and dissociation processes of correlated triplet pairs (TT) in SF by means of pressure-dependent UV/vis and fluorescence spectrometry and fluorescence lifetime and nanosecond transient absorption measurements. The photophysical properties obtained under hydrostatic pressure suggested distinct acceleration of the SF dynamics by microenvironmental desolvation, the volumetric compaction of the TT intermediate based on solvent reorientation toward an individual triplet (T1 ), and pressure-induced shortening of T1 lifetimes. This study provides a new perspective on the control of SF by hydrostatic pressure as an attractive alternative to the conventional control strategy for SF-based materials.